Early surrogates of outcome after thrombectomy in posterior circulation stroke. (28th August 2022) - Kniep, Helge; Bechstein, Matthias; Broocks, Gabriel; Brekenfeld, Caspar; Flottmann, Fabian; van Horn, Noel; Geest, Vincent; Faizy, Tobias D.; Deb‐Chatterji, Milani; Alegiani, Anna; Thomalla, Götz; Gellißen, Susanne; et al.
Abstract: Background: Early surrogates for functional outcome in anterior circulation stroke have been described with the National Institute of Health Stroke Scale (NIHSS) at 24 h being reported as the most accurate metric. We compare discriminatory power of established definitions of early neurological improvement (ENI) and NIHSS scores at admission and 24 h to predict functional outcome at 90 days after thrombectomy in posterior circulation stroke (PCS). Methods: All patients enrolled in the German Stroke Registry (June 2015–December 2019) with PCS and at least vertebral or basilar artery occlusions were included. NIHSS admission, 24 h and ENI definitions (improvement of 8/10 NIHSS points or 0/1 NIHSS points at 24 h) were compared for predicting functional outcome at 90 days. Favourable and good outcome were defined as modified Rankin Scale (mRS) 0–2 and 0–3. Multivariable logistic regression analysis was conducted to identify factors impairing predictive power. Results: Three hundred and eighty‐seven patients were included. NIHSS 24 h had the highest discriminative power with receiver operator characteristics area under the curve of 0.87 (95% confidence interval: 0.83; 0.90) for good and 0.89 (0.85; 0.92) for favourable outcome; optimal cut‐off values were ≤9 and ≤5. Higher age (odds ratio = 1.10 [1.05; 1.16]), adverse events during treatment (9.46 [1.52; 72.5]) and until discharge (18.34 [2.33; 172]) and high NIHSS scores at 24 h (1.29 [1.10; 1.53]) were independent predictors for turning the outcome prognosis from good (mRS ≤3) to poor (mRS ≥4). Conclusions: NIHSS 24 h ≤9 points serves best as surrogate for good functional outcome after thrombectomy in PCS. Advanced age, severe neurological symptoms at admission and adverse events decrease its predictive value.